2014
DOI: 10.1073/pnas.1323818111
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire nanocomputer as a finite-state machine

Abstract: Implementation of complex computer circuits assembled from the bottom up and integrated on the nanometer scale has long been a goal of electronics research. It requires a design and fabrication strategy that can address individual nanometer-scale electronic devices, while enabling large-scale assembly of those devices into highly organized, integrated computational circuits. We describe how such a strategy has led to the design, construction, and demonstration of a nanoelectronic finite-state machine. The syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 28 publications
1
93
0
Order By: Relevance
“…[3][4][5]19,20 To this end, we recently introduced a dielectric charge-trapping shell structure on nanowire transistor elements and showed that by modulating the charge state in the dielectric layers the transistor could be programmed as "active" or "inactive" within a specific logic window. Integration of these nanowire device elements into a crossbar array 19,20 further yielded a basic module or tile that could be used for proposed array-based architecture. 1,3−5 There are several important features critical to a programmable crossbar circuit.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[3][4][5]19,20 To this end, we recently introduced a dielectric charge-trapping shell structure on nanowire transistor elements and showed that by modulating the charge state in the dielectric layers the transistor could be programmed as "active" or "inactive" within a specific logic window. Integration of these nanowire device elements into a crossbar array 19,20 further yielded a basic module or tile that could be used for proposed array-based architecture. 1,3−5 There are several important features critical to a programmable crossbar circuit.…”
mentioning
confidence: 99%
“…Compared to charge-based programming of active/inactive nodes, 19,20 which has analogies to flash memory, 24 resistive switch elements provide potential advantages in terms of nonvolatility or retention, scaling, and programming speed and endurance. 21−23 First, in the resistive switch the state change is largely due to a local structural/ composition change in the material between switch electrodes, and the retention is often projected to be beyond years.…”
mentioning
confidence: 99%
See 3 more Smart Citations